New Blind Filter Protocol: An Improved Privacy-Preserving Scheme for Location-Based Services. (16th June 2020) - Li, Zhidan; Li, Wenmin; Gao, Fei; Yu, Ping; Zhang, Hua; Jin, Zhengping; Wen, Qiaoyan
Abstract: Location-based services have attracted much attention in both academia and industry. However, protecting user's privacy while providing accurate service for users remains challenging. In most of the existing research works, a semi-trusted proxy is employed to act on behalf of a user to minimize the computation and communication costs of the user. However, user privacy, e.g. location privacy, cannot be protected against the proxy. In this paper, we design a new blind filter protocol where a user can employ a semi-trusted proxy to determine whether a point of interest is within a circular area centered at the user's location. During the protocol, neither the proxy nor the location-based service provider can obtain the location of the user and the query results. Moreover, each type of query is controlled by an access tree and only the users whose attributes satisfy this access tree can complete the specific type of query. Security analysis and efficiency experiments validate that the proposed protocol is secure and efficient in terms of the computation and communication overhead.